TINJAUAN KEBIJAKAN TENTANG CORPORATE SOCIAL RESPONSIBILITY (CSR) DI KABUPATEN SINTANG - Evy, Marselina (Universitas Kapuas Sintang, 2024)
The aim of this research is to identify about program of corporate social responsibility in a regional development efforts. This research was examined in regarding the implementation of a regional policies relating to corporate social responsibility at Sintang Regency. This research used a qualitative method. The data obtained from interviews and CSR document. The researcher interviews with the Sintang Regency government. This research used interactive analysis by Miles and Hubberman. The result of research shows that, implementation of coordination of CSR by regency government is not optimal. By the time, implementation of regional policies is slowly. The synchronization step that has been done has not been effective. The implementation process, in that mean is the CSR practice is not accordance with Sintang regent regulation number 54, 2016 about Corporate Social Responsibility and the prime mover development of Sintang Regency. The CSR practice has not focused on community empowerment efforts. Keywords: Corporate Social Responsibility, CSR Practice, Implementation of regional policies